ANALISIS STRATEGI PEMASARAN YANG DI GUNAKAN PABRIK SUMBER REJO DALAM MENINGKATKAN PENJUALAN BERAS - Supratman, Aldi; Wening Tyas; Arini Rosa Sinensis (Jurnal Manajemen dan Pemasaran, 2025)
This research aims to analyze the marketing strategy implemented by the Sumber Rejo Factory in an effort to increase rice sales. In the context of intense market competition, there is an urgent need for UMKM to adapt to technological developments and change traditional marketing strategies to digital in order to remain relevant in this modern era (Maliki, 2021; , (Asharudin & Dewi, 2021). The research method used is a qualitative approach with data collection techniques through interviews and case studies at the Sumber Rejo Factory (Nurasyiah & Fadli, 2023). The results of the research show that the implementation of the marketing mix, which includes product, price, promotion and distribution, is a key factor that contributes to increasing rice sales (Santu et al., 2024; , Putri et al., 2024). In addition, the use of digital platforms such as social media has proven effective in expanding market reach and increasing brand awareness (Asharudin & Dewi, 2021). The conclusions of this research indicate that the Sumber Rejo Factory needs to continue to develop adaptive and innovative marketing strategies in order to compete optimally, as observed in the best practices of other businesses in the same sector (Agustin et al., 2024). Thus, the resulting strategic recommendations are expected to help the Sumber Rejo Factory increase its competitiveness in the local rice market.